(untitled) (European Journal of Child Development, Education and Psychopathology, 2014)
Sexuality education constitutes a social, political and methodological challenge, entailing comprehensive solutions that encompass various sectors of society. The connection between education and health is extremely important to the debate about sexuality, particularly with relation to adolescents and youth. Government initiatives, the fruit of public policies, cannot dispense with the vast experience accumulated by civil society organizations in activism and methodological design of social interventions. The alliance between government and civil society organizations is extremely fruitful for both sectors, as it enhances their respective and cumulative impact. The objective of this article is to analyze the pilot course of a capacity development project for professional educators in gender and sexuality, grounded in the partnership between a civil society organization and the public school system in the city of Salvador, Brazil. Our analysis will address the limits, accomplishments and challenges faced by the project, which was implemented in order to promote gender equity among girls and boys in Brazilian schools.